Effect of Nd:Yag Laser Hyaloidotomy for Premacular Subhyaloid Haemorrhage - Lamichhane, Gynendra; Singh, Sweta (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Premacular subhyaloid hemorrhage is a common condition leading to severe sudden vision loss in various conditions.This study investigated the effects of drainage of premacular subhyaloid hemorrhage into the vitreous with Nd:YAG laser treatment. Photodisruption with Zeiss Nd.Yag laser done in the inferior part of the the hemorrhage to create hole in ILM for gravitational drainage of blood in vitreous. A rapid resolution of subhyaloid hemorrhage with improvement of visual acuity was achieved in all patients treated with Nd:YAG laser posterior hyaloidotomy, without evidence of damage to the retina or choroid. Nd:YAG laser posterior hyaloidotomy is simple, effective, safe and non invasive procedure for draining a premacular hemorrhage into the vitreous cavity and to avoid vitreoretinal surgery and complication related to long standing macular toxicity by blood. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 51-53